Experimental investigations on in-plane and out-of-plane flexural performance of UHPC beams with wet joints - Chen, Shijing; Liu, Bin; Wu, Zhiqiang; Liu, Hanyu; Han, Bin; Yan, Banfu (Frontiers in Materials, 2025)
Prefabricated bridges have emerged as a significant trend in modern bridge construction. To study the in-plane and out-of-plane flexural performance of ultra-high-performance concrete (UHPC) beams with wet joints, in-plane and out-of-plane specimens with different curing methods for UHPC wet joints were designed and fabricated. The cracking loads, peak loads, and crack development of the specimens were recorded and analyzed. The test results revealed that all specimens experienced flexural failure with damage to the normal section. Moreover, the flexural capacity of the jointed specimens reached a minimum of 91% of the complete specimen’s flexural capacity. The joints influenced the cracking behavior of in-plane specimens but had minimal impact on out-of-plane specimens. Chiseling, increasing steel fiber contents and welding longitudinal steel bars with short steel bars reduced structural damage and decrease in stiffness. The different curing methods for UHPC at the joints have little impact on stiffness and flexural capacity of the joint specimens but played a positive role in improving ductility. Finally, a calculation method for flexural capacity considering the contribution of web steel bars is provided.